Pengenalan Huruf Hijaiyah Menggunakan Nyanyian Dalam Metode Tilawati PAUD Di Taam Nurul Barokah Cisayong - Setiawati, Cucu (Journal of Islamic Education for Early Childhood, 2024)
Considering the importance of understanding al-quran as a guide in life, learning to read al-quran requires effective and appropriate methods to be given to children. For this reason, this study was conducted with the aim of describing how the application of the tilawati PAUD method at TAAM Nurul Barokah Cisayong in introducing hijaiyah letters to early childhood using singing. This research is a qualitative research with a descriptive approach. Data collection techniques were carried out by means of observation and interviews. The data obtained was analyzed using triangulation techniques. The results showed that learning the al-quran in introducing hijaiyah letters to early childhood using singing in the tilawati method is an effective method in learning the al-quran for early childhood. The tilawati method combines a classical approach in familiarizing the introduction of hijaiyah letters and an individual approach to the fluency of the students' reading. The tilawati method is favored by children because it is easy to remember and certainly interesting for children, because this method uses songs and songs that are unique so that children get high motivation to learn to read the al-quran. Keywords: Al-Quran Learning, Tilawati Method, Early Childhood, Hijaiyah Letters